2015
DOI: 10.1016/j.juro.2014.09.099
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory System of Highly Trained Dogs Detects Prostate Cancer in Urine Samples

Abstract: A trained canine olfactory system can detect prostate cancer specific volatile organic compounds in urine samples with high estimated sensitivity and specificity. Further studies are needed to investigate the potential predictive value of this procedure to identify prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 29 publications
4
107
0
1
Order By: Relevance
“…[25][26][27][28] Methodologies for in-vitro training and testing of DADs for the detection of hypoglycemia are being refined. 3 This is the first study to assess trained dog alerts concurrently with blinded CGM.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Methodologies for in-vitro training and testing of DADs for the detection of hypoglycemia are being refined. 3 This is the first study to assess trained dog alerts concurrently with blinded CGM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Taverna et al [34] reported the capability of two highly trained dogs to discriminate urine samples of patients having prostate cancer from healthy ones, achieving a diagnostic accuracy in terms of both sensitivity and specificity of over 97%, and subsequently for detecting biochemical recurrence following radical prostatectomy [35]. …”
Section: Introductionmentioning
confidence: 99%
“…2 The ability of the dogs was tested on urine samples from subjects with low risk to metastatic PC and samples from healthy controls in a study with a cross-sectional design for diagnostic accuracy. Dog 1 achieved 100% sensitivity and 98.7% specificity, and dog 2 achieved 98.6% sensitivity and 97.6% specificity.…”
Section: Dog Olfactory System Detects Prostate Cancermentioning
confidence: 99%